A Case of an Extensive Keratocystic Odontogenic Tumor in the Mandible Reconstructed with a Custom-Made Total Joint Prosthesis. Issue 2 (June 2018) - Farzad, Payam
The use of virtual surgical planning and computer-aided design/computer-aided manufacturing has previously been reported to enhance the planning for the reconstruction of mandibular continuity defects and to reduce surgical time. Reported is a case of a large keratocystic odontogenic tumor (KOT) affecting right hemimandible including the condylar neck. This case was initially reconstructed with a condyle-bearing reconstruction plate, but because of fatigue fracture 15 years later, a new reconstruction with a custom-made total joint temporomandibular prosthesis was performed.